Предмет: Математика,
автор: Айгерима11
1563
1){х+4у/9-х-2у/3=0
{х+7у/4+х+у/6=4
Ответы
Автор ответа:
0
Упростим 1 уравнение:
(х+4у):9=(х-2у):3
(х+4у)*3=(х-2у)*9
3х+12у=9х-18у
30у=6х
у=1/5х
Упростим 2 уравнение:
(х+7*1/5х):4+(х+1/5х):6=4
3/5х+1/5х=4
4/5х=4
х=4:4/5
х=5
Подставим уравнения в систему:
у=1/5х
х=5
у=1/5*5
х=5
у=1
х=5
(х+4у):9=(х-2у):3
(х+4у)*3=(х-2у)*9
3х+12у=9х-18у
30у=6х
у=1/5х
Упростим 2 уравнение:
(х+7*1/5х):4+(х+1/5х):6=4
3/5х+1/5х=4
4/5х=4
х=4:4/5
х=5
Подставим уравнения в систему:
у=1/5х
х=5
у=1/5*5
х=5
у=1
х=5
Похожие вопросы
Предмет: Окружающий мир,
автор: hddjwbfo
Предмет: Литература,
автор: galievvadim1
Предмет: Литература,
автор: leratemnyh
Предмет: Физика,
автор: 1212132332